2010
DOI: 10.2105/ajph.2009.185462
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Health and Mental Health of People Living With HIV/AIDS: 12-Month Assessment of a Behavioral Intervention in Thailand

Abstract: Objectives-. People living with HIV (PLH) in Thailand face multiple stressors. We examined findings from a randomized controlled intervention trial designed to improve the quality of life of PLH in Thailand. Methods-.A total of 507 PLH were recruited from four district hospitals in northern and northeastern Thailand and were randomized to an intervention group (n = 260) or a standard care group (n = 247). Computer-assisted personal interviews were administered at baseline, 6, and 12 months.Results-At baseline,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 39 publications
2
53
0
1
Order By: Relevance
“…This study uses data from a randomized controlled family intervention trial in Thailand (Li et al, 2010; Li et al, 2012). Initial screenings of children of PLH were conducted in the district hospitals by healthcare workers and research staff.…”
Section: Methodsmentioning
confidence: 99%
“…This study uses data from a randomized controlled family intervention trial in Thailand (Li et al, 2010; Li et al, 2012). Initial screenings of children of PLH were conducted in the district hospitals by healthcare workers and research staff.…”
Section: Methodsmentioning
confidence: 99%
“…Four studies have directly assessed shame among PLWH, and each reported a medium to large effect size between shame and depressive symptoms (Bennett, Hersh, Herres, & Foster, 2015; DeMarco, 1998; Li et al, 2010; Rodkjaer, Laursen, Balle, & Sodemann, 2010). These studies of American, Danish, and Thai PLWH included adolescents through older adults, and both men and women.…”
Section: Shame and Depressive Symptomsmentioning
confidence: 99%
“…Shame also predicted worse physical health a year later among PLWH (Li et al, 2010) and is associated with greater physical symptoms and reduced health-related quality of life among PLWH in cross-sectional studies (DeMarco, 1998; Persons, Kershaw, Sikkema, & Hansen, 2010). …”
Section: Shame and Physical Healthmentioning
confidence: 99%
“…Most CBIs have been implemented in the U.S. and other wealthy nations; however, a few studies of CBI in less wealthy nations have yielded promising results. For example, in Thailand, a study of a culturally adapted CBI demonstrated improvement in general health and mental health (Li et al, 2010). Integrating behavioral interventions with HIV care for HIV-positive individuals with co-morbid mental health and substance use disorders significantly reduces psychiatric symptoms and improves medication adherence (K. Whetten et al, 2006).…”
Section: Treatment For Ptsd and Other Sequelae Of Trauma In People LImentioning
confidence: 99%